PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, DISIPLIN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI (Studi pada Balai Pelestarian Cagar Budaya DIY) - Septianingsih, Heny; Kirana, Kusuma Chandra; Subiyanto, Didik (Jurnal Fokus Manajemen Bisnis, 2020)
The objective of the researcher is to examine the variables of transformational leadership, work discipline and organizational commitment to employee performance at the DIY Preservation Hall. The population in this study were employees of the DIY Conservation Center. Sampling using Slovin formula (Sugiyono, 2011: 87), sampling technique using stratified random sampling method with 75 respondents.Data analysis techniques using classical assumption testing: normality test, multicollinearity test, heteroscedasticity test, autocorrelation test. Hypothesis testing using the T test, F test, coefficient of determination R2, beta coefficient of standardization. The results showed that the Transformational Leadership variable had a significant positive effect on Employee Performance, Work Discipline had a significant positive effect on employee performance and the presence of organizational commitment had a significant positive effect on employee performance at the Conservation Center DIY.